Theoretical studies of hydrogen bonding interactions between novolac resin and DMP-30. Issue 115 (8th December 2016) - Jian, Zhang; Yang, Xiaomeng; Chen, Dong; Qian, Yang
Abstract : Hydrogen bonding complexes of novolac resin and DMP-30 were investigated with dispersion-corrected density functional theory at the B3LYP-D3/6-31G** level. The results show that the complexes can be used as a latent curing agent for epoxy resin. Abstract : Hydrogen bonding complexes of novolac resin and DMP-30 was investigated with dispersion-corrected density functional theory at the B3LYP-D3/6-31G** level. The results show that novolac resin and DMP-30 could form stable complexes which can be used as a latent curing agent of epoxy resin through hydrogen bond interactions. Three stable configurations (I, II, III) are obtained by the calculation, and their interaction energies range from −27.92 to −31.69 kcal mol −1 with the basis set superposition error (BSSE) correction. The stabilization energies of the complexes are mainly attributed to the interaction between lone pairs of the carbonyl N and O atoms in DMP-30 and the anti-bonding orbital of O–H in novolac resin. The hydrogen bonding interactions of the complexes were investigated by geometrical parameters, interaction energy, frequency analysis, atoms in molecules (AIM) analysis and natural bond orbital (NBO) analysis, and thus its latent curing mechanism was preliminary interpreted.